2017
DOI: 10.1042/ebc20170058
|View full text |Cite
|
Sign up to set email alerts
|

Host–pathogen interactions and subversion of autophagy

Abstract: Macroautophagy (‘autophagy’), is the process by which cells can form a double-membraned vesicle that encapsulates material to be degraded by the lysosome. This can include complex structures such as damaged mitochondria, peroxisomes, protein aggregates and large swathes of cytoplasm that can not be processed efficiently by other means of degradation. Recycling of amino acids and lipids through autophagy allows the cell to form intracellular pools that aid survival during periods of stress, including growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 106 publications
2
31
0
Order By: Relevance
“…Studies in other systems have described pathogen virulence factors that suppress host autophagy, for example through removing LC3 conjugation from the autophagosomal membrane. 9 Perhaps because another pathogen suppressed LGG-2-mediated autophagy in its evolutionary past, C. elegans evolved a separate pathway for clearance that functions here in the absence of LGG-2 to clear N. ironsii. Regardless of the reason, it is clear that HW animals have a pathway separate from LGG-2 that mediates clearance of N. ironsii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in other systems have described pathogen virulence factors that suppress host autophagy, for example through removing LC3 conjugation from the autophagosomal membrane. 9 Perhaps because another pathogen suppressed LGG-2-mediated autophagy in its evolutionary past, C. elegans evolved a separate pathway for clearance that functions here in the absence of LGG-2 to clear N. ironsii. Regardless of the reason, it is clear that HW animals have a pathway separate from LGG-2 that mediates clearance of N. ironsii.…”
Section: Discussionmentioning
confidence: 99%
“…6 When autophagy is used to degrade intracellular pathogens it is called xenophagy. [7][8][9][10] Xenophagy often begins with localization of host ubiquitin to intracellular microbes, followed by localization of autophagy proteins, formation of an autophagosome to enclose the microbe, and then fusion with a lysosome to degrade microbial cargo. Initial studies of the role for autophagy in immunity focused on xenophagy, although it is now appreciated there are 'non-canonical' forms of autophagy that also promote anti-microbial defense.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the critical role of autophagy in pathogen control is evident from the fact that viruses and bacteria have evolved numerous strategies to curtail and subvert autophagic processes [31]. As an example, it was recently shown that selective xenophagy of Mycobacterium tuberculosis surface protein such as Rv1468c can be targeted for ubiquitination, followed by p62 recruitment, and the subsequent delivery of the Rv1468c-ubiquitin-p62 complex to LC3-decorated autophagosomes for selective degradation [32].…”
Section: Catabolism Repurposed For Survivalmentioning
confidence: 99%
“…Perhaps expectedly, this has led to an evolutionary arms race between host and pathogens, which have developed a range of mechanisms to evade destruction. These host-pathogen interactions have been the subject of much research, providing valuable information not only about key virulence factors and important infections, but also about the underlying host molecular mechanisms that they subvert (Campoy and Colombo, 2009;Kimmey and Stallings, 2016;Casanova, 2017;McEwan, 2017;Sharma et al, 2018;Siqueira et al, 2018;Sudhakar et al, 2019;Wu and Li, 2019;Xiong et al, 2019;Hu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%